Hepatic sarcoidosis: Clinical characteristics and outcome - Christiana Graf; Jeannette Arncken; Christian M. Lange; Katharina Willuweit; Jörn M. Schattenberg; Jessica Seessle; Julia Lang-Meli; Tobias Böttler; Julia Dietz; Nils Wetzstein; Antonia Mondorf; Johannes Vermehren; et al. (JHEP Reports, 2021)
Background & Aims: Clinical manifestation of hepatic involvement in sarcoidosis can vary from asymptomatic disease to severe complications such as cirrhosis and portal hypertension. However, data on hepatic sarcoidosis are limited, and evidence-based recommendations are lacking. Our study aimed to assess the features and clinical course of hepatic sarcoidosis in a predominantly Caucasian cohort. Methods: We performed a retrospective study including all patients with hepatic sarcoidosis between 2004 and 2020 in 5 German centres. The median follow-up time was 36 months (range 0.0–195). Data on demographic parameters, clinical manifestations, diagnostic test results, treatment, and outcome were collected. Results: A total of 1,476 patients with sarcoidosis and 62 patients with hepatic involvement (4.2%) were identified. Of the patients, 51.6% were female, and 80.6% were Caucasian. Most patients were asymptomatic and were observed to have a cholestatic pattern of liver enzyme elevations. Cirrhosis was detected in 9 patients (14.5%), of whom 6 developed clinical manifestations of portal hypertension. Fifty-four patients were medically treated, most commonly with glucocorticoids (69.4%) or ursodeoxycholic acid (UDCA) (40.3%). Levels of alkaline phosphatase (ALP) decreased by 60.8% on average from baseline in patients treated with glucocorticoids and by 59.9% in patients treated with UDCA. Seventeen patients received treatment augmentation with a second line agent, of whom 8 patients normalised ALP levels during follow-up. None of the patients underwent liver transplantation or developed hepatocellular carcinoma (HCC). Three of the patients died during follow-up owing to liver-related complications. Conclusions: Hepatic involvement in sarcoidosis was found in 4.2% of patients with sarcoidosis and was clinically significant in 14.5% of those. These findings highlight the importance of early identifying, monitoring, and treating hepatic sarcoidosis, given its increased mortality when associated with end-stage liver disease. Lay summary: Clinical diagnostic and surveillance of hepatic involvement in sarcoidosis has not been standardised, and management of hepatic involvement is a clinical challenge, since it remains poorly characterised in many ways. Our results show that one-third of patients with hepatic sarcoidosis presented with clinically significant portal hypertension, 14.5% suffered from cirrhosis, and 3 patients died owing to liver-related complications. Regarding pharmacological treatment options, corticosteroids and UDCA were the medical agents most frequently used, and both of them have been shown to induce biochemical response in the majority of patients. These findings highlight the importance of correctly and early identifying hepatic involvement in sarcoidosis, because of the potentially progressive course of disease.